5z+3z=6z-7

Simple and best practice solution for 5z+3z=6z-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z+3z=6z-7 equation:


Simplifying
5z + 3z = 6z + -7

Combine like terms: 5z + 3z = 8z
8z = 6z + -7

Reorder the terms:
8z = -7 + 6z

Solving
8z = -7 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
8z + -6z = -7 + 6z + -6z

Combine like terms: 8z + -6z = 2z
2z = -7 + 6z + -6z

Combine like terms: 6z + -6z = 0
2z = -7 + 0
2z = -7

Divide each side by '2'.
z = -3.5

Simplifying
z = -3.5

See similar equations:

| x^3-4x^2-207x+630=0 | | 5x=88 | | 5x+2y+2z=7 | | 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 | | (X+1)+(3x+1)+(x+1)=180 | | P(x)=-0.1x^5+3.8x^4+5000 | | 7-x=-2x-5 | | 0.4+1.5=2.2-15x | | 2n^2+2n-42=0 | | 5(3+5x)-1=89 | | 10-2a+4=32 | | 3=-4n+3n | | 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j | | x-34=-14 | | 4X-30+X+20=180 | | 8x^3-60x^2+150x-854=0 | | x-27=-17 | | -27=-5(9a+6) | | 12+8r=6-10r | | 10x+3(4x-2)=6 | | 7y+3(y-6)=6(y+1)-3 | | 12x-(8x-9)=45 | | 6x-7x+2=12 | | 2x-8+10=3x-7 | | 5*sin(14x)=5*cos(7x) | | 13x^2-8x-20=0 | | -2y+9x=3 |

Equations solver categories